Digitalisasi Pendampingan Bank Sampah Sekolah Berbasis Boarding School dalam Mendukung Pendidikan Lingkungan Hidup Berkelanjutan - Andi Zulitsnayarti Mardhani Syam; Thamrin Tahir; Alfiana Damasinta; Muhammad Ilyas Thamrin Tahir; Ratna S (Jurnal Teknologi dan Informatika, 2026)
Waste management issues in boarding school environments represent one of the environmental challenges that require educational, participatory, and sustainable solutions. Students’ activities that take place continuously throughout the day within the school and dormitory areas contribute to the increasing generation of domestic waste, including plastic waste, disposable sanitary pads, cosmetic packaging, and other household waste. On the other hand, waste management practices in schools are still predominantly conducted manually, resulting in less effective and poorly organized environmental management systems. This community service program aimed to support sustainable environmental education through the digitalization of the school waste bank assistance program at SMA Putri Luqman Al-Hakim. The program was implemented using participatory and educational approaches consisting of observation and problem identification, socialization and education, implementation of waste bank digitalization, as well as monitoring and evaluation stages. The activities included waste segregation education, the application of the 3R concept (reduce, reuse, recycle), and assistance in using a digital-based waste deposit recording system through online spreadsheets and simple applications. The results demonstrated an improvement in students’ understanding and participation in school waste management activities. Furthermore, the implementation of the digital system contributed to a more organized, transparent, and easily monitored waste bank administration process. The program also played a role in fostering environmentally responsible behavior and improving students’ digital literacy. Therefore, the digitalization of school waste banks can serve as an alternative strategy to support environmental education and sustainable school environmental management.